2019
DOI: 10.32771/inajog.v7i1.818
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic and Nutritional Determinants of Birth Weight in Coastal Areas

Abstract: Abstract Objective :  To identify socio-demographic and nutritional determinant associated with birth weight in coastal areas. Method : A cross sectional study using simple random sampling method. Data of labour in coastal areas of Kendari City was analyzed. Total of 215 women who aterm delivery in Community Health Centre of Mata, Nambo and Abeli on January to December 2016 were included in this study. Birth weight was examined in association with independent variable as maternal age, education, oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…They also had lower levels of education than those who were not malnutrition. It was similar with previous study which found that maternal age and maternal education level were determinants of infant birth weight in coastal areas (Saimin, Azizah, et al, 2019). Previous study also showed that malnutrition in children is one of the problems that occur in coastal areas.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…They also had lower levels of education than those who were not malnutrition. It was similar with previous study which found that maternal age and maternal education level were determinants of infant birth weight in coastal areas (Saimin, Azizah, et al, 2019). Previous study also showed that malnutrition in children is one of the problems that occur in coastal areas.…”
Section: Resultssupporting
confidence: 91%
“…There was 8.8% under the red line status of children under five years old. Under the red line status is at risk of suffering from malnutrition (Dinkes, 2016;Saimin, Azizah, & Wicaksono, 2019). Therefore, this study aimed to assess the risk of LBW on the incidence of malnutrition in children under five years old in the coastal areas of Kendari City.…”
Section: Introductionmentioning
confidence: 99%
“…Birth weight is very important factor of a newborn's health and future health or wellbeing. It indicates intrauterine growth conditions and health during pregnancy period [1] [2] Low birth weight defined by the World Health Organization (WHO) as a birth weight less than 2500 grams regardless of gestational age. [3][4] [5].…”
Section: Introductionmentioning
confidence: 99%